Differential Responses of Dominant Plants to Grazing in Typical Temperate Grassland in Inner Mongolia - Dongli Wan; Yongqing Wan; Yunfeng Wang; Tingting Yang; Fang Li; Wuriliga; Yong Ding (Agriculture, 2022)
Leymus chinensis, Stipa grandis, Artemisia frigida, and Cleistogenes squarrosa are the dominant plant species in typical temperate grasslands in Xilingol. Intensive studies related to overgrazing, which resulted in a dominant plant shift, have been carried out in recent years, but the ways in which these four species respond to different grazing intensities remain elusive. In this study, the contents of primary metabolites, secondary metabolites, and phytohormones in the leaves of these species under five grazing intensities were assayed and compared. The results showed that A. frigida contained higher amounts of lignin, while C. squarrosa contained higher amounts of total flavonoids than the other species. Leymus chinensis showed a different accumulation of cellulose and tannin in response to grazing, compared with the other three species. Stipa grandis and A. frigida increased in soluble protein contents in response to different grazing treatments. In particular, the contents of phytohormones, such as abscisic acid, salicylic acid, and gibberellins, were markedly changed under grazing. Leymus chinensis exhibited different abscisic acid and gibberellins accumulation patterns compared with the other species, under the different grazing intensities. Patterns of salicylic acid accumulation were similar (except under light and moderate grazing intensities in A. frigida) among the four species. The results indicated that the four species differed in adaptive strategies to cope with the different grazing intensities, and phytohormones played important roles in coordinating the regulation of their growth and grazing tolerance. This study provides a foundation for elucidating the mechanisms of overgrazing-induced degradation of the Xilingol grassland.